Vegetable oils as carbon and energy source for Aureobasidium melanogenum in batch cultivation. Issue 6 (4th December 2018) - van Nieuwenhuijzen, Elke J.; Sailer, Michael F.; van den Heuvel, Edwin R.; Rensink, Stephanie; Adan, Olaf C. G.; Samson, Robert A.
Abstract: Dark homogenous fungal‐based layers called biofinishes and vegetable oils are key ingredients of an innovative wood protecting system. The aim of this study was to determine which of the vegetable oils that have been used to generate biofinishes on wood will provide carbon and energy for the biofinish‐inhabiting fungus Aureobasidium melanogenum, and to determine the effect of the oil type and the amount of oil on the cell yield. Aureobasidium melanogenum was cultivated in shake flasks with different types and amounts of carbon‐based nutrients. Oil‐related total cell and colony‐forming unit growth were demonstrated in suspensions with initially 1% raw linseed, stand linseed, and olive oil. Oil‐related cell growth was also demonstrated with raw linseed oil, using an initial amount of 0.02% and an oil addition during cultivation. Nile red staining showed the accumulation of fatty acids inside cells grown in the presence of oil. In conclusion, each tested vegetable oil was used as carbon and energy source by A. melanogenum . The results indicated that stand linseed oil provides less carbon and energy than olive and raw linseed oil. This research is a fundamental step in unraveling the effects of vegetable oils on biofinish formation. Abstract : A raw linseed oil, olive oil, and stand linseed oil were used as carbon and energy source for Aureobasidium melanogenum during shake flask cultivation. The results indicated that the stand linseed oil provides less carbon and energy than the olive and raw linseed oil.